Good distant outcome of treatment of a patient with advanced gastric cancer - Stanisław Głuszek; Piotr Bryk (Studia Medyczne, 2015)
The case of a patient is presented who had undergone surgical procedure of total gastrectomy, including the greater and lesser omentum, spleen, tail of the pancreas, splenic flexure of the colon, part of the diaphragm, and D2 lymphadenectomy, due to advanced gastric cancer T4bN3M0. The study covers a 9-year period of observations and check-up examinations performed on this patient. During all that time the patient remained in a good general condition, without features of cancer recurrence. Despite unfavourable prognosis in patients with clinical advancement of gastric cancer stage 3C, long-term survivals happen, such as in the case presented by the researchers. Most probably this is related with the biology of the tumour, which has not been fully recognised, and many prognostic factors of a given cancerous disease.